2020
DOI: 10.1016/j.fbp.2020.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of solvent composition and its interaction with ultrasonic energy on the ultrasound-assisted extraction of phenolic compounds from Mango peels (Mangifera indica L.)

Abstract: Ultrasound has been used to intensify the extraction of phenolic compounds from many agro-food products. However, there is still a lack of understanding on how the ultrasonic energy is influenced by blends of different solvents and how this impacts the extraction process. This work studied the effect of ethanol, acetone and hexane blends on the ultrasonic energy generated during the extraction of phenolic compounds from Mango peel, using an ultrasonic-assisted extraction (UAE) and a conventional solvent extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(65 citation statements)
references
References 57 publications
3
57
3
2
Order By: Relevance
“…is study confirmed that ultrasonic extraction is the most rapid and efficient technique, which allows to significantly increase the rate of phenolic content compared to other methods studied [25]. According to several studies, the quality of the phenolic compounds and the total concentration of polyphenols in several matrices extracted by ultrasound depends on the quantity and the polarity of the solvent used, the ultrasonic intensity [26], the extraction temperature [27], and the extraction time [28]. e aim of this work was to maximize the obtained yield and total phenolic contents from L. stoechas extracted by ultrasound method.…”
Section: Introductionsupporting
confidence: 64%
“…is study confirmed that ultrasonic extraction is the most rapid and efficient technique, which allows to significantly increase the rate of phenolic content compared to other methods studied [25]. According to several studies, the quality of the phenolic compounds and the total concentration of polyphenols in several matrices extracted by ultrasound depends on the quantity and the polarity of the solvent used, the ultrasonic intensity [26], the extraction temperature [27], and the extraction time [28]. e aim of this work was to maximize the obtained yield and total phenolic contents from L. stoechas extracted by ultrasound method.…”
Section: Introductionsupporting
confidence: 64%
“…Maceration is a traditional and simple method that allows for the obtaining of good extraction efficiencies involving long extraction periods (24-72 h) and (assisted by ultrasound) generally increases the extraction of bioactive compounds, which decreases extraction times, as shown by numerous studies of different residues [13,16,28,29]. However, the extraction efficiency depends mainly on process variables such as sonication time, amplitude, solvent type, particle size and extracting material.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies show that mango peel presents a majority of bioactive compounds rather than kernel and endocarp, attributed to the differences in its composition [4,13,25]. The mango residue's polyphenol compounds are good donors of electrons, generating high antioxidant capacities [32].…”
Section: Residue Typementioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound has been proven to be an intensified extraction process for the extraction of oil from olive fruit, soybean, and flaxseed (46,47). It is also employed for the extraction of bioactives from different parts of plants, fruits, and vegetables (48)(49)(50)(51). Ultrasonic-assisted filtration process is also very effective and is of importance to dairy and beverage industries.…”
Section: Applicationsmentioning
confidence: 99%